Sero-epidemiological survey of Coxiella burnetii in livestock and humans in Tana River and Garissa counties in Kenya - Mwololo, D.; Nthiwa, Daniel; Kitala, P.; Abuom, T.; Wainaina, M.; Kairu-Wanyoike, S.; Lindahl, Johanna F.; Ontiri, Enoch; Bukachi, S.; Njeru, I.; Karanja, J.; Sang, R.; et al. (2022)
Background: Coxiella burnetii is a widely distributed pathogen, but data on its epidemiology in livestock, and human populations remains scanty, especially in developing countries such as Kenya. We used the One Health approach to estimate the seroprevalance of C. burnetii in cattle, sheep, goats and human populations in Tana River county, and in humans in Garissa county, Kenya. We also identified potential determinants of exposure among these hosts.